Construction of car porch steel structure / Muhammad Danish Haykal Mohd Tarmizi - Mohd Tarmizi, Muhammad Danish Haykal (Universiti Teknologi MARA, Perak, 2018)
Roof is a structure that provide shelter for human and its properties. The Strnctui-e is the important part of the roof. Therefore, this repott will discuss about the construction of car porch structure. This rep011 was conducted based on a car porch structure that were constructed at Surau An-Nur in Seri Alam, Johor. The purpose of the report is to identify the method of production steel truss and its installation. This report will also detennine the equipment that was used to for fabrication and installation of the steel truss on site. The method to collect infotmation for completing this report was by observation and unstmctured-interviews with the site supervisor in-charge and related individuals. In short, this report contains the work of the construction of pad foundation, production of steel trusses and installing the ttuss on site with the list of equipment that was used with the specification that was stated in.